A cowboy's touch - Hunter, Denise, 1968- (Hunter, Denise, 1968- Big sky romance., 2011)
After she leaves her high-pressure job to live with her aunt on a Montana ranch, Abigail Jones, working as a nanny for Wade Ryan, the ranch's owner, begins a relationship with him, but Wade's first priority is to protect his daughter and keep his past a secret.